2017
DOI: 10.3802/jgo.2017.28.e85
|View full text |Cite
|
Sign up to set email alerts
|

Survival of gynecological cancers in Turkey: where are we at?

Abstract: ObjectiveTo investigate the 5-year relative survival rates in gynecological cancers diagnosed and treated in Turkey by year 2009 and to compare the results with developed countries.MethodsData of patients diagnosed for ovarian, corpus uteri or cervix uteri cancer at year 2009 are collected from 9 national cancer registry centers. Date of deaths are retracted from governmental Identity Information Sharing System (KPS). In order to calculate relative survival rates, national general population mortality tables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
1
6
0
5
Order By: Relevance
“…Endometrial cancer was third most common cancer in our series, accounting for 9.7%; this result is similar to that of Engbang et al who found 11.6% in 2015 in the Littoral region of Cameroon and Agboeze et al found a proportion of 10.1% in Nigeria in 2015 [6, 13]. This proportion, however, is lower than those found in developed countries, especially the 40.1% reported in Japan by Yamagami et al in 2017 and 45.9% in Turkey according to Gultekin et al in 2017 [14, 15]. This difference could be explained by the fact that, unlike cervical cancer, where screening methods are known and screening programs are operational and effective in these countries, there is no method of screening for endometrial cancer.…”
Section: Discussionsupporting
confidence: 85%
“…Endometrial cancer was third most common cancer in our series, accounting for 9.7%; this result is similar to that of Engbang et al who found 11.6% in 2015 in the Littoral region of Cameroon and Agboeze et al found a proportion of 10.1% in Nigeria in 2015 [6, 13]. This proportion, however, is lower than those found in developed countries, especially the 40.1% reported in Japan by Yamagami et al in 2017 and 45.9% in Turkey according to Gultekin et al in 2017 [14, 15]. This difference could be explained by the fact that, unlike cervical cancer, where screening methods are known and screening programs are operational and effective in these countries, there is no method of screening for endometrial cancer.…”
Section: Discussionsupporting
confidence: 85%
“…All patients were staged according to the SEER stage (localized, regional, and distant). According to SEER rules, cervix uteri FIGO stage I; FIGO stages II, III; and FIGO stage IV are classified as localized, regional, and distant disease [ 15 16 ]. We also used X-tile 3.6.1 software (Yale University, New Haven, CT, USA) to transform the value of the age at diagnosis into a categorical variable ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bu nedenle ek olarak fertilitenin korunması gibi özel durum ve güçlükleri de bünyesinde barındırır. 2012 yılı itibari ile serviks, corpus uteri ve over kanserleri tüm kadın kanserlerinin %16'sını, kanser nedenli ölümlerin %14'ünü teşkil eder (2). Yaş, enfeksiyöz nedenler (human papilloma virus, human immunodeficiency virus, diğer cinsel yolla bulaşan enfeksiyözler), reprodüktif ve hormonal nedenler (menarş, menapoz, doğum sayısı, emzirme, koit yaşı, partner durumu, endojen hormonal ajanlar vb), sigara, önceki kanserler, medikal durum ve alınan tedaviler, obezite, immun sistem durumu, aile öyküsü-genetik gibi çok sayıda etken jinekolojik kanser etyolojisi içinde yer almaktadır.…”
Section: Introductionunclassified
“…), human papillomavirus (HPV) aşı programları, erken belirtilerin tanınmasına olanak sağlayacak önlemler (tarama programları gibi) ile önlenebilir veya erken tanı alabilir. Araştırmamızda 2009-2013 yılları arasında kliniğimizde opere edilen jinekolojik malignitelerin orijin, yaş dağılımı, evre dağılımı, bazı epidemiyolojik özellikler açısından retrospektif değerlendirilmesi amaçlanmıştır (2).…”
Section: Introductionunclassified